LATAR BELAKANG PENDIDIKAN, UKURAN USAHA, PEMBERIAN INFORMASI DAN SOSIALISASI TERHADAP PEMAHAMAN UMKM DALAM MENYUSUN LAPORAN KEUANGAN BERDASARKAN SAK EMKM (STUDI PADA UMKM DI WILAYAH KECAMATAN CIPARAY) - Silvi Sri Nurhayati; Ahmad Muhammad Ryad; Ahmad Bahrudin Doni Boro (Prodi Akuntansi, 2022)
This research aims to know how much the influence of educational background, business size, providing information and socialization on the understanding of MSMEs in compiling financial reports based on SAK EMKM on wholesale businesses in Ciparay District, Bandung Regency. Respondents are 58 MSMEs in Ciparay District by using questionnaire method. The results showed that: 1) There was no significant effect of educational background on the understanding of MSMEs in compiling financial reports based on SAK EMKM with tcount 1.419 < ttable 2.00488. 2) There is a significant effect of business size on the understanding of MSMEs in compiling financial reports based on SAK EMKM with tcount 4.157 > ttable 2.00488. 3) There is a significant effect of providing information and socialization on the understanding of MSMEs in compiling financial reports based on SAK EMKM with a value of tcount 7.514 > ttable 2.00488. 4) There is a significant influence of educational background, business size, providing information and socialization (on the understanding of MSMEs in preparing financial reports based on SAK EMKM with a value of Fcount 21,224 > Ftable 2,776. The value of the coefficient of determination of educational background, size of business, presenting information and socialization has an effect of 51.6% on the understanding of MSMEs in preparing financial reports based on SAK EMKM